ANALISIS KOMPARATIF USAHATANI SAWI CAISIM PADA MUSIM TANAM YANG BERBEDA DI LAHAN PERTANIAN PERKOTAAN: Comparative Analysis of Caisim Mustard Farming Across Different Growing Seasons in Urban Farming Areas - Mirfatul Hidayah; Agung Widya Wardhana; Wawan Apzani (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
Caisim mustard (Brassica rapa var. parachinensis),  is one of the most commercially important leafy vegetables in Indonesia. It is the most commonly sold mustard green in traditional markets because of its strong consumer preference and high market demand. The purpose of this research is to analyze the cost and benefit of mustard farmer caisim Across Different Growing Seasons in Urban Farming Areas; This research uses descriptive method. The Unit of analysis in this research is farmers and mustard farmer caisim in Mataram city. This research was carried out in two villages namely Ampenan captured subdistricts of Pejarakan Karya and North of Ampenan. Determination of a sample of research done by Purposive Sampling by the consideration that the village was a centre of farming mustard caisim in Mataram city. The results of this research show that; (1) Total acceptance of mustard farmer caisim in the dry season is Rp. 2.472.168,750/LLG per one time process of cropping. Acceptance in the rainy season is Rp. 2.657.0,16,667/LLG per one time planting process. The Total cost of production required to produce mustard caisim per attempt once the production process during the dry season is Rp. 604.355 3,305/LLG and in the rainy season is Rp. 565.280,417/LLG. So the net income or profit earned from mustard farmer caisim during the dry season which is Rp. 1.867.812 501,055/LLG per one time planting process. As for the rainy season is Rp. 2.091.736,249/LLG per planting processes; (2). The value of R/C ratio on mustard farmer caisim during the dry season which is of 4, 091 and in the rainy season for 4,700 so that it can be said that the farmer already efficient caisim mustard greens; For farmers to make mustard farmer caisim as one option for farmers because it is worth trying to economically and efficiently.